2011
DOI: 10.1038/oby.2010.254
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive‐Behavioral Treatment of Nonalcoholic Fatty Liver Disease: A Propensity Score‐Adjusted Observational Study

Abstract: The effectiveness of cognitive‐behavior treatment (CBT) in nonalcoholic fatty liver disease (NAFLD), largely related to overweight/obesity and considered the hepatic expression of the metabolic syndrome (MS), has so far been tested in very limited samples. In a tertiary referral center, consecutively observed NAFLD subjects were offered a CBT program aimed at weight loss and increased physical activity, based on 13 group sessions; 68 cases entered the treatment protocol, those who refused (n = 82) were given r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 49 publications
1
26
0
4
Order By: Relevance
“…The modest but significant reduction of liver enzymes is likely to reflect decreased hepatic triglyceride accumulation [30], as commonly observed in nonalcoholic fatty liver disease entering specific activity programs, also independent of weight loss [31,32]. It should be viewed in the context of the chronic liver disease associated with obesity and diabetes, where intense behavioral treatment [33], also leading to improved glucose control, reduced insulin levels and improved insulin sensitivity [34], is expected to stop liver disease progression [33,35]. …”
Section: Discussionmentioning
confidence: 99%
“…The modest but significant reduction of liver enzymes is likely to reflect decreased hepatic triglyceride accumulation [30], as commonly observed in nonalcoholic fatty liver disease entering specific activity programs, also independent of weight loss [31,32]. It should be viewed in the context of the chronic liver disease associated with obesity and diabetes, where intense behavioral treatment [33], also leading to improved glucose control, reduced insulin levels and improved insulin sensitivity [34], is expected to stop liver disease progression [33,35]. …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have tested the effectiveness of lifestyle modifications in NAFLD (Table 4) (58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73) ; only a few are based on solid behavioral strategies, not simply on intensive counseling for healthy diet and habitual physical activity. Overall, 7%-10% weight loss is achieved in the majority of cases, accompanied by a remarkable normalization of liver enzymes and a systematic reduction of liver fat, measured by either surrogate algorithms or USG or MRI.…”
Section: Strategies To Improve Adherencementioning
confidence: 99%
“…Their effectiveness in promoting weight loss has been demonstrated on long-term follow-up. 7 Programs of cognitive-behavioral therapy have also been applied in NAFLD; 8 weight loss through healthy and restrictive diet, coupled with habitual physical activity, has been reported to reduce NAFLD progression in small pilot trials, [9][10][11] and a large prospective intervention study confirmed that weight loss is associated with histologic improvement on repeated liver biopsy. 12 Unfortunately, these programs require dedicated teams and support, which are rarely found in liver units.…”
Section: Introductionmentioning
confidence: 99%